Avaliação técnica de semeadoras adubadoras para plantio direto de milho no estado de Minas Gerais - Santos, Ariston Pinto (2006)
With the objective of technically evaluating three sowing machines for no-tillage farming of corn, an experiment was established in the area of the Agricultural Engineering of the UFLA, under Typic Distroferric Red Latosol clayey (LVdf), by utilizing the three following sowing machines: S1 - Semeato SHM 11/13; S2 - John Deere RT 907 and e S3 - John Deere RT 907, with different furrow opening systems for fertilizer placement., moving at three different speeds of 1.38, 1.8, 2.22 m.s-1. The variables quantified were: biomass, moisture and soil resistance to penetration, stand plants m-1, plant emergence velocity; sowing uniformity (double, acceptable, failures), sowing depth, mechanical damages, seed germination, skidding, average power on the draw bar, average power per sowing mechanism, hourly and specific fuel consumption and theoretical field capacity. A statistical design in randomized blocks with split plot was adopted. From the results obtained, it was possible to conclude that, as regards the operational system of the tractor-sowing assembly, significant differences occurred among the three assemblies as to the power on the bar and fuel consumption. As for skidding and power, no significant difference occurred between assemblies 1 and 2, presenting lower value, differing from assembly 3. There were no statically significant differences for emergence velocity of plants, sowing depth, mechanical damages and ermination. Significant differences occurred concerning the variable stand, the highest values being designed to assemblies 1 and 3 and the lowest one designed to assembly 2.